A Visual Analysis Model Integrating Design Perspectives and Elements in Students’ Imaginative Drawings - Muh. Andis Hidayatullah; Nawung Asmoro Girindraswari; Muhamad Romadoni; Muhammad Ahsin Maulana (Universitas Negeri Medan, 2026)
This study examines how perspective and nirmana principles are integrated in imaginative drawings produced by Primary School Teacher Education (PGSD) students in visual arts learning. Previous discussions of students’ drawings in art education have often treated perspective as a technical matter and nirmana as a list of visual elements. This study addresses that limitation by positioning both concepts as an integrated visual literacy framework for reading spatial construction, compositional order, and pedagogical readiness among prospective elementary school teachers. A descriptive qualitative design was employed using visual artwork analysis, classroom observation, documentation, and literature study. Ten student artworks were selected through criterion-based purposive sampling because they represented diverse themes, visual complexity, and varied applications of perspective and nirmana. The analysis sheet was developed from perspective indicators, nirmana principles, and stages of art criticism, then strengthened through expert judgment and inter-rater discussion. The findings reveal three patterns of visual construction: narrative-spatial, decorative-dense, and thematic-symbolic. Students demonstrated strength in visual imagination, local themes, color exploration, rhythm, and thematic unity; however, they still showed weaknesses in horizon awareness, vanishing point consistency, scale relations, proportional accuracy, focal point, and visual hierarchy. The study proposes a Perspective-Nirmana Integration model as a conceptual contribution for analyzing imaginative drawings in visual arts learning. Pedagogically, the findings imply that PGSD visual arts instruction should connect imaginative exploration with systematic exercises in spatial representation, composition, visual hierarchy, and reflective critique.